ANALISIS PERTUMBUHAN DAN STRUKTUR EKONOMI MAKRO DI KOTA BANDUNG - Nahwan, Darwin (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
Bandung has become an important center for creative and technology industries in Indonesia. The existence of leading universities, research centers, and business incubators has formed an innovation ecosystem that encourages the birth of startups and technology companies based in this city. Along with increasing challenges and opportunities in a rapidly changing global environment, a strong and developing economic sector is a vital key in ensuring the country's sustainability and prosperity. This study aims to analyze the growth and macroeconomic structure in the city of Bandung. The research method used is quantitative. Research data comes from the Central Bureau of Statistics and local government reports, to identify patterns and trends in urban economic development. Analysis shows that the city of Bandung has experienced rapid economic growth in the last few decades. The creative and technological industries, as well as tourism, are the main drivers of economic growth. The activities in Bandung in relation to the economy of West Java throughout 2019-2022 are the area of exchange, accommodation and cafes as well as the areas of communication and conversion, because with the presence of development (+) and commitment (-) is actually meant with the assumption that this movement expands its commitment will be an outstanding area